Does Pancreatic Fistula Affect Long-Term Survival after Resection for Pancreatic Cancer? A Systematic Review and Meta-Analysis - Andrea Grego (MDPI AG, 2021)
Background: The impact of postoperative pancreatic fistula (POPF) on survival after resection for pancreatic ductal adenocarcinoma (PDAC) remains unclear. Methods: The MEDLINE, Scopus, Embase, Web of Science, and Cochrane Library databases were searched for studies reporting on survival in patients with and without POPF. A meta-analysis was performed to investigate the impact of POPF on disease-free survival (DFS) and overall survival (OS). Results: Sixteen retrospective cohort studies concerning a total of 5019 patients with an overall clinically relevant POPF (CR-POPF) rate of 12.63% (n = 634 patients) were considered. Five of eleven studies including DFS data reported higher recurrence rates in patients with POPF, and one study showed a higher recurrence rate in the peritoneal cavity. Six of sixteen studies reported worse OS rates in patients with POPF. Sufficient data for a meta-analysis were available in 11 studies for DFS, and in 16 studies for OS. The meta-analysis identified a shorter DFS in patients with CR-POPF (HR 1.59, p = 0.0025), and a worse OS in patients with POPF, CR-POPF (HR 1.15, p = 0.0043), grade-C POPF (HR 2.21, p = 0.0007), or CR-POPF after neoadjuvant therapy. Conclusions: CR-POPF after resection for PDAC is significantly associated with worse overall and disease-free survival.